2018
DOI: 10.20289/zfdergi.414100
|View full text |Cite
|
Sign up to set email alerts
|

A-sınıfı Buharlaşma Kabından Olan Buharlaşma Miktarının Penman ve Priestley-Taylor (PT) Modelleri ile Tahmini

Abstract: Bu çalışmada; çok yıllık meteorolojik veriler mevcut olmadığında, daha önce meteoroloji istasyonu olmayan bir yere yeni bir istasyon kurulduğunda ya da ivedi olarak günlük buharlaşma verisi gerektiğinde buharlaşma modellerinin günlük iklim verileri kullanılarak gerçekleştirilen tahminleme süreçleri iki yıllık bir zaman periyodunda araştırılmıştır. Materyal ve Metot: Buharlaşma miktarını veren Penman (1948) ve Priestley-Taylor (PT) (1972) olarak seçilen iki model kullanılmıştır. A sınıfı buharlaşma kabı (Epan)'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The r (NSE) values for the Penman and Priestly-Taylor methods were 1.07 (0.48) and 1.05 (0.42), respectively. These results are consistent with those of [12], who also used these methods on measured data at the Samsun station. They noted that the Penman method tends to overestimate E pan compared to the Priestly-Taylor method.…”
Section: A Evaporation Estimation By Penman and Priestley-taylor Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The r (NSE) values for the Penman and Priestly-Taylor methods were 1.07 (0.48) and 1.05 (0.42), respectively. These results are consistent with those of [12], who also used these methods on measured data at the Samsun station. They noted that the Penman method tends to overestimate E pan compared to the Priestly-Taylor method.…”
Section: A Evaporation Estimation By Penman and Priestley-taylor Methodssupporting
confidence: 91%
“…Some recent studies on evaporation can be mentioned into three groups. The first group of studies were concerned about suggesting the empirical methods with needing less input variables that makes the best estimation for their study areas [5][6][7][8][9][10][11][12][13][14]. The second group compares the performance of artificial intelligence models, such as artificial neural networks and fuzzy logic with that of empirical equations, highlighting the potential of these models [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the all-former methods provided successful results, although the performance was better in the GEP method in the simulations. In a similar manner, Sezer et al [21] estimated the daily and monthly evaporation losses for class A pans in Samsun with the Kohler-Nordenson-Fox (KNF) and Christiansen models during the 2012-2013 time period. The results show that the EP values were acquired using the KNF model with a higher performance and the Christiansen model overestimated the evaporation.…”
Section: Introductionmentioning
confidence: 99%